IMPLEMENTASI KEBIJAKAN E-VOTING DALAM PEMILIHAN KEPALA DESA DI KABUPATEN MEMPAWAH PROVINSI KALIMANTAN BARAT - Sri Maryuni; R.L Sitorus (Universitas Lambung Mangkurat, 2020)
This research intended to explain the implementation of e-voting policy on the head of the village election at Mempawah Region Kalimantan Barat. The election was done for twice occasions, at 2017 and 2018. Purpose of the research was to describe and analyze the implementation process of e-voting policy on the head of the village election at Mempawah Region Kalimantan Barat. The research method in this paper was using qualitative methods with descriptive technique. In order to gain information on the implementation process of e-voting policy on the head of the village at Mempawah Region, Kalimantan Barat. Charles O. Jones (1996: 296) theory stated that the implementation process of e-voting policy was based on three pillars, which are the organization, interpretation, and application. We found that there were some obstacles in implementing e-voting policy, such as the lack of electronic facilities quantity and quality that supported the policy, there were also a lot of people which has not been registered in the e-voting application, and some negatives perception of the e-voting process. Researchers have several recommendations to overcome the problems. First, the government should do socialization on the e-voting election. Second, an improvement in the e-voting system especially on the issue of the person with disabilities. Third, evaluate the regulation. Lastly, increase the coordination among stakeholders within bureaucracy and village staff in order to have a better database of the elector.